Neutrophil hyperactivation correlates with Alzheimer's disease progression. Issue 2 (20th February 2018) - Dong, Yuan; Lagarde, Julien; Xicota, Laura; Corne, Hélène; Chantran, Yannick; Chaigneau, Thomas; Crestani, Bruno; Bottlaender, Michel; Potier, Marie‐Claude; Aucouturier, Pierre; Dorothée, Guillaume; Sarazin, Marie; et al.
Abstract : Objective: Recent studies have underlined the effect of systemic inflammation on the pathophysiology of Alzheimer's disease (AD). Neutrophils are key components of early innate immunity and contribute to uncontrolled systemic inflammation if not tightly regulated. The aim of our study was to fully characterize human circulating neutrophils at different disease stages in AD. Methods: We analyzed neutrophil phenotypes and functions in 42 patients with AD (16 with mild cognitive impairment and 26 with dementia), and compared them to 22 age‐matched healthy subjects. This study was performed directly in whole blood to avoid issues with data interpretation related to cell isolation procedures. Results: Blood samples from AD patients with dementia revealed neutrophil hyperactivation associated with increased reactive oxygen species production and increased levels of intravascular neutrophil extravascular traps. The homeostasis of circulating neutrophils in these patients also changed: The ratio between the harmful hyperreactive CXCR4 high /CD62L low senescent and the CD16 bright /CD62L dim immunosuppressive neutrophil subsets rose in the later stage of the disease. These abnormalities were greater in fast‐decliner than in slow‐decliner patients. Interpretation: Our results indicate that the inflammatory properties of circulating neutrophils shift as the percentage of aged neutrophils expands in patients with AD—changes that may play an instrumental role in establishing systemic chronic inflammation. Most important, our data strongly suggest that the neutrophil phenotype may be associated with the rate of cognitive decline and may thus constitute an innovative and prognostic blood biomarker in patients with AD. Ann Neurol 2018;83:387–405